Fas ligand gene-carrying adeno-5 AdEasy viruses can be efficiently propagated in apoptosis-sensitive human embryonic retinoblast 911 cells - Watzlik, Andrea; Dufter, Christoph; Jung, M.; Opelz, Gerhard; Terness, Peter (Gene therapy, 2000)
Recent reports have pointed out the difficulties in generating recombinant adenoviral vectors expressing FasL using eukaryotic cells. In the present study we cloned the murine FasL (mFasL) gene into the pCA14 or pShuttle vectors and recombined them with the adeno-5 virus backbone pBHG10 or pAdEasy-1 in eukaryotic (911 cells) or prokaryotic (E. coli) cells, respectively. Recombination of pCA14-mFasL with pBHG10 in Fas-carrying 911 cells leads to rapid expression of mFasL and cell death by apoptosis before virus replication is initiated. The same effect is observed when 911 cells are transfected with the pCA14-mFasL shuttle vector only. If recombination (pShuttle-mFasL with pAdEasy-1) is performed first in bacteria and 911 cells are transfected thereafter with recombined AdEasy-mFasL, virus production starts immediately and the cells survive longer. The resulting AdEasy-mFasL viruses are able to infect other eukaryotic cells and induce expression of functional mFasL. This study describes a method for efficient generation of recombinant FasL adeno-5 viruses in eukaryotic cells. The method may be generally suitable for producing viruses carrying deleterious genes. Gene Therapy (2000) 7, 70-74.
Gesehen am 19.02.2021